Effect of supplementation with berberine on dyslipidemias in humans: A systematic review (Research, Society and Development, 2021)
Objective: to describe in a systematic review, the outcomes of clinical trials related to supplementation with berberine and dyslipidemia in humans. Methodology: The search for the articles was carried out in the Pubmed, ScienceDirect, Cochrane and Lilacs databases. The PICO strategy (patient, intervention, comparison and outcomes) was used to define the guiding question for this review. The terms “Coptis chinensis OR Berberine” AND “Dyslipidemia OR Dyslipoproteinemias” were used for the bibliographical survey. Included in this systematic review were randomized, double-blind, placebo controlled clinical trials, published in English, with no year limit of publication, which evaluated the effect of supplementation with berberine on the influence on lipid profiles in humans with dyslipidemia, without gender restriction, age and ethnicity. Results: After the screening process, removal of duplicate articles and analysis of the inclusion criteria, 10 articles were identified as eligible for this systematic review. Discussion: most of the included clinical trials found a reduction in the levels of total cholesterol, triglycerides and LDL. The outcomes of all studies were similar, indicating that berberine and its respective bioactive compounds have potential in the treatment of dyslipidemia. Conclusion: The results of this systematic review provide evidence of the benefits of berberine supplementation on the lipid profile, total cholesterol, triglycerides and the reduction of LDL levels in dyslipidemic individuals. However, further intervention studies are needed to extrapolate the results of this study in different populations, as well as to standardize doses of berberine extract for supplementation.